Long-term ecological safety of paraquat use in tropical soils - Dyson, J. (Malaysian Plant Protection Society, 2018)
The amount of paraquat that can be in soil without causing effects was measured in tropical soils to determine the long-term ecological safety of paraquat use with respect to soil. The capacity of three mineral soils from Thailand and Malaysia to deactivate paraquat's biological effects by adsorption was measured using a laboratory assay known as the 'Strong Adsorption Capacity-Wheat Bioassay' (SACWB). Subsequently, paraquat was applied to field plots at rates below, and just above, the laboratory measured SAC-WB value by incorporating paraquat down to nominal cultivation depths 15 and 20 cm. The applications of paraquat were equivalent to hundreds of times agronomic application rates, so unlikely to occur from normal practice. After application, typical local crops were grown in the field plots, e.g. cassava, maize, pineapple, peanut and soybean to assess whether residues of paraquat had any effects on crops and earthworms. Soil samples were also taken to determine the paraquat residue levels in soil. The results showed that even the highest residues of paraquat in soil had no statistically significant long tern effects on crops or earthworms, demonstrating its ecological safety and suitability for sustainable agriculture.